Efektivitas terhadap Sanksi Pidana Bagi Perusahaan yang Menunggak Iuran Jaminan Sosial Ketenagakerjaan: Studi di BPJS Ketenagakerjaan Gorontalo - Wahyu Nurhardiyanto Hulopi; Ramdhan Kasim; Roby W. Amu (Majelis: Jurnal Hukum Indonesia, 2025)
Law enforcement against criminal acts of companies that do not pay and deposit BPJS contributions based on the Social Security Organizing Agency Law. To determine and analyze the factors that influence the enforcement of criminal acts against companies that do not pay and deposit contributions to the Social Security Organizing Agency. Where this research method is normative juridical and empirical juridical. Normative juridical research is conducted by examining library materials or secondary materials only. This research is also carried out by describing, examining and explaining and analyzing normative provisions associated with the research nisi. While empirical research is based on the reality that researchers get in the field. From the results of this study it is known that the application of criminal sanctions against companies that are in arrears of employment social security contributions in Gorontalo Province has not shown optimal effectiveness or in other words less effective, this is based on the findings showing that the application of criminal sanctions against violations of participation in the employment social security program has not been effective, because 64.48% of workers have not received the protection of the program. Factors that influence companies that do not pay and deposit contributions to the Social Security Organizing Agency, namely: Economic and Financial Factors of the Company, Level of Knowledge and Compliance, Perception of Benefits and Risks, Access and Ease of Payment, Law Enforcement and Sanctions, Social and Cultural Factors.